2016
DOI: 10.1177/1538192716652500
|View full text |Cite
|
Sign up to set email alerts
|

Community College Developmental Education Services: Perspectives of Spanish-Speaking Latino Early Childhood Educators

Abstract: The purpose of this single-case study was to understand the perceptions of Latino Spanish-speaking English learners on the efficacy of developmental education services at a Western U.S. community college. The primary data collection method was in-depth individual interviews of a purposeful sample of nine successful students. Findings indicated that participants relied on Spanish instruction for comprehensible context, but needed consistent education support services from a culturally responsive institution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition to financial barriers, immigrant-origin students and their families often lack knowledge on how to navigate the U.S. higher education system (Chlup et al, 2018) and may struggle to locate resources on campus (Mahaffy & Pantoja, 2012). English language proficiency also presents a challenge for some immigrant-origin youth (Arbelo-Marrero & Milacci, 2016; Eberly, 2018; Mahaffy & Pantoja, 2012; Suárez-Orozco et al, 2010). Growing up with higher poverty rates, they are also more likely to attend schools that are underresourced and segregated, impacting their academic performance and access to information about college (Suárez-Orozco et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to financial barriers, immigrant-origin students and their families often lack knowledge on how to navigate the U.S. higher education system (Chlup et al, 2018) and may struggle to locate resources on campus (Mahaffy & Pantoja, 2012). English language proficiency also presents a challenge for some immigrant-origin youth (Arbelo-Marrero & Milacci, 2016; Eberly, 2018; Mahaffy & Pantoja, 2012; Suárez-Orozco et al, 2010). Growing up with higher poverty rates, they are also more likely to attend schools that are underresourced and segregated, impacting their academic performance and access to information about college (Suárez-Orozco et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge deficits ranged from lack of information about the college choice process and what is needed to be a competitive college applicant (e.g., Engstrom, 2008;Kouyoumdjian et al, 2017;Lauby, 2017;Leinbach & Bailey, 2006) to lack of knowledge about resources to help navigate college and requirements for college graduation (Cerezo et al, 2009;Freeman, 2017;Mahaffy & Pantoja, 2012;Person & Rosenbaum, 2006). Another major challenge was the lack of English language skills (Conway, 2010;Eberly, 2018;Engstrom, 2008;Smith, 2010). For example, Arbelo-Marerro and Milacci (2016) found that "English language learning played a vital role in the persistence behaviors of participants" (p. 22) who were Latinx nontraditional students enrolled at Hispanic serving institutions.…”
Section: Negative Depictionsmentioning
confidence: 99%
“…Because one of the challenges of providing developmental education in undergraduate coursework is students' frustration with the amount of time they must spend in developmental courses, which are not credited toward their respective degrees (Eberly, 2018;Park & Ngo, 2021;Rutschow & Schneider, 2011), some scholars have argued for accelerating developmental education sequences to increase students' academic momentum (e.g., Daugherty et al, 2019;Hodara & Smith Jaggars, 2014). Schudde and Keisler (2019) and Boatman (2021), for example, both found a strong relationship between participating in accelerated developmental education and key indicators of academic momentum, including completing college-level math courses and total credit accumulation.…”
Section: Academic Momentummentioning
confidence: 99%